2004
DOI: 10.1021/ja0493547
|View full text |Cite
|
Sign up to set email alerts
|

Mild, Aqueous, Aerobic, Catalytic Oxidation of Methane to Methanol and Acetaldehyde Catalyzed by a Supported Bipyrimidinylplatinum−Polyoxometalate Hybrid Compound

Abstract: We have demonstrated that a bipyrimidinylplatinum-polyoxometalate, [Pt(Mebipym)Cl2]+[H4PV2Mo10O40]-, supported on silica is an active catalyst for the aerobic oxidation of methane to methanol in water under mild reaction conditions. Further oxidation of methanol yields acetaldehyde. The presence of the polyoxometalate is presumed to allow the facile oxidation of a Pt(II) intermediate to a Pt(IV) intermediate and to aid in the addition of methane to the Pt catalytic center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(151 citation statements)
references
References 10 publications
5
140
0
4
Order By: Relevance
“…The reactions involved in the formation of acetaldehyde are shown below, according to previous investigations35 CH4oxidantCH3OHoxidantHCHO CH4+CH3OHoxidantCH3CH2OHoxidantCH3CHO CHnormal4+HCHOoxidantCH3CHO CH3OH+HCHOdehydrationCH3CHO …”
Section: Resultsmentioning
confidence: 99%
“…The reactions involved in the formation of acetaldehyde are shown below, according to previous investigations35 CH4oxidantCH3OHoxidantHCHO CH4+CH3OHoxidantCH3CH2OHoxidantCH3CHO CHnormal4+HCHOoxidantCH3CHO CH3OH+HCHOdehydrationCH3CHO …”
Section: Resultsmentioning
confidence: 99%
“…After calcination the reaction with methane was performed (at 150°C for 25 min in 8% CH 4 in He with total flow 25 mL/min) in a batch mode. Activation and reaction were performed in a quartz flow cell equipped with a UV-vis-NIR transparent window.…”
Section: Experimental Partmentioning
confidence: 99%
“…The direct conversion of methane to methanol and formaldehyde holds one of the greatest challenges in heterogeneous catalysis [1][2][3][4]. Methane is an important fossil feedstock and its direct partial oxidation to oxygenates is challenging for thermodynamic reasons.…”
Section: Introductionmentioning
confidence: 99%
“…[8] These properties have led to new binary catalytic systems. We have reported that a platinum(II) bipyridinium-polyoxometalate binary complex is effective for the aerobic oxidation of methane [9] and nanoparticles stabilized by polyoxometalates lead to improved catalytic activity in carbon-carbon coupling reactions, [10] and improved selectivity in aerobic alkene epoxidation reactions. [11] Palladium nanoparticles have often been used in catalytic applications; [12] their stabilization with alkylthiols is less commonly used, [13] because of the ingrained perception that alkylthiols and thiolates are poisons that inhibit catalysis.…”
mentioning
confidence: 99%